Mechanisms of Heart Pump Function Regulation among Immature Animals (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: Studies were carried out to study the peculiarities of the pumping function of the heart of immature rats subjected to various regimes of motor activity at earlier stages of individual development. Methodology: White mongrel laboratory rats were used in the experiments, which were conditionally divided into two experimental test subgroups, and were subjected to forced muscle training-swimming and normal vivarium conditions, and parameters of the heart pumping function were recorded at 14, 42, and 70 days. Results and Discussion: The carried out studies allow to draw the conclusion that the heart rate (HR) and the shock volume of blood (SVB) among the animals kept in the regime of free motor activity (FrMA) from 14 to 70 days of age will largely change from 42 to 70 days of life. With a systematic muscular training, organized at earlier stages of postnatal development of rats, the pumping function of the heart and the mechanisms of its regulation undergo significant changes at the initial stage, i.Ðµ., from 14 to 42 days. Conclusions: The HR, the SVB, and the mechanisms of their regulation of small laboratory animals kept in the regime of FrMA will change to a greater extent in the age range from 42 to 70 days of life, and among the rats, susceptible to systematic muscle training, the parameters of heart pumping function and the mechanisms of its regulation undergo significant changes from 14 to 42 days of animals life.